2004
DOI: 10.17660/actahortic.2004.657.27
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Plum Pox Virus in Japanese Plums in Spain

Abstract: The Japanese plum (Prunus salicina) industry is economically important in Spain and in other countries with Mediterranean climate. P. salicina was described as a natural host of Plum pox virus (PPV) in Spain in 1984, where the 'Red Beaut' cultivar become an important source of inoculum and it spread the virus to apricots and plums along the Spanish Mediterranean coast. The spatial and temporal spread of PPV was monitored along a twelve year period in a collection of 41 Japanese plum cultivars, planted in Luche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 1 publication
(1 reference statement)
6
20
0
Order By: Relevance
“…In the experimental orchard May had the highest aphid populations, this is in agreement with previous data (Cambra et al 2006a). A. spiraecola was the most probable significant vector of PPV in European and Japanese plums in the experimental orchard, as has been reported for Japanese plums in other Mediterranean Spanish Prunus growing areas (Cambra et al 2004;2006a). Results from other Mediterranean countries showed that A. gossypii is the most abundant aphid in apricot orchards in Spain and Greece (Avinent et al 1989(Avinent et al , 1991(Avinent et al , 1993Varveri et al 2004) and A. spiraecola is the predominant aphid species in apricot orchards in south-eastern France (Labonne and Dallot 2006) In non-Mediterranean climate areas, such as Pennsylvania (USA), the most abundant aphid species caught on peach trees were Rhopalosiphum maidis (Filch) and A. spiraecola.…”
Section: Discussionsupporting
confidence: 74%
“…In the experimental orchard May had the highest aphid populations, this is in agreement with previous data (Cambra et al 2006a). A. spiraecola was the most probable significant vector of PPV in European and Japanese plums in the experimental orchard, as has been reported for Japanese plums in other Mediterranean Spanish Prunus growing areas (Cambra et al 2004;2006a). Results from other Mediterranean countries showed that A. gossypii is the most abundant aphid in apricot orchards in Spain and Greece (Avinent et al 1989(Avinent et al , 1991(Avinent et al , 1993Varveri et al 2004) and A. spiraecola is the predominant aphid species in apricot orchards in south-eastern France (Labonne and Dallot 2006) In non-Mediterranean climate areas, such as Pennsylvania (USA), the most abundant aphid species caught on peach trees were Rhopalosiphum maidis (Filch) and A. spiraecola.…”
Section: Discussionsupporting
confidence: 74%
“…The observed in peach orchard blocks annual disease incidence between 2% and 6% (Dallot, Gottwald, Labonne, & Quiot, ), is in contrast to the much greater spread of PPV‐D and PPV‐M strains recorded by Llacer, Avinent, and Hermoso de Mendoza (), Adamolle, Boeglin, Labonne, Candresse, and Quiot (), Cambra et al. () and Varveri (). Both biotic (virus characteristics, transmission efficiency, dynamics of vector populations, susceptibility of host plant) and abiotic (climate, landscape characteristics) factors impact sharka disease prevalence and spread (Rimbaud et al., ).…”
Section: Discussionmentioning
confidence: 93%
“…Finally, three Japanese plums (‘Black Star’, ‘Calita’, and ‘Laroda’) were tolerant, without (or mild) symptoms, and a low percentage of plants were ELISA positive. Cambra et al. (2004) did not observe symptoms in ‘Laroda’ either.…”
Section: Resultsmentioning
confidence: 77%
“…2004). However, ‘Black Amber’ and ‘Ozark Premier’ have shown only slight symptoms in field conditions (Cambra et al. 2004), and ‘Black Amber’ was even classified as resistant (Ramming and Cociu 1991).…”
Section: Resultsmentioning
confidence: 99%